1999
DOI: 10.1073/pnas.96.7.4149
|View full text |Cite
|
Sign up to set email alerts
|

NADH-quinone oxidoreductase: PSST subunit couples electron transfer from iron–sulfur cluster N2 to quinone

Abstract: The proton-translocating NADH-quinone oxidoreductase (EC 1.6.99.3) is the largest and least understood enzyme complex of the respiratory chain. The mammalian mitochondrial enzyme (also called complex I) contains more than 40 subunits, whereas its structurally simpler bacterial counterpart (NDH-1) in Paracoccus denitrificans and Thermus thermophilus HB-8 consists of 14 subunits. A major unsolved question is the location and mechanism of the terminal electron transfer step from iron-sulfur cluster N2 to quinone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
127
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 38 publications
(34 reference statements)
7
127
0
Order By: Relevance
“…This was, in part, based on photoaffinity labeling of NuoB from membranes of Paracoccus nitrificans and Thermus thermophilus with a 3 H-labeled pyridaben analog (31). In the same study, both rotenone and piericidin A prevented binding of the 3 H-labeled pyridaben analog (another pesticide) (31). This is compatible with the results of the present study, where compound A-resistant mutants had missense mutations in either the C terminus of nuoD or in nuoB.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was, in part, based on photoaffinity labeling of NuoB from membranes of Paracoccus nitrificans and Thermus thermophilus with a 3 H-labeled pyridaben analog (31). In the same study, both rotenone and piericidin A prevented binding of the 3 H-labeled pyridaben analog (another pesticide) (31). This is compatible with the results of the present study, where compound A-resistant mutants had missense mutations in either the C terminus of nuoD or in nuoB.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, they suggested that the binding site for the polar head of ubiquinone is located at the interface of NuoD and NuoB. This was, in part, based on photoaffinity labeling of NuoB from membranes of Paracoccus nitrificans and Thermus thermophilus with a 3 H-labeled pyridaben analog (31). In the same study, both rotenone and piericidin A prevented binding of the 3 H-labeled pyridaben analog (another pesticide) (31).…”
Section: Discussionmentioning
confidence: 95%
“…Ubiquinone-analogous complex I inhibitors like 2-decyl-4-quinazolinyl amine (DQA), 1 rotenone, and pyridaben are thought to prevent the terminal electron transfer step from cluster N2 to ubiquinone (7). Using a trifluoromethyl derivative of pyridaben for photoaffinity labeling, the PSST subunit was identified as high-affinity target (11), suggesting that this subunit is in close vicinity to the ubiquinone binding site of complex I.…”
mentioning
confidence: 99%
“…This poses the problem of how the redox chemistry taking place in the peripheral arm can drive proton translocation across the membrane arm. Evidence from different laboratories (10,11) and the identification of several pathogenic mutations (12) suggested a key mechanistic role for the 49-kDa, PSST, and TYKY subunits. Based on these indications and a well established homology (13) between the 49-kDa and PSST subunits of complex I and the large and small subunits of [NiFe] hydrogenases, we proposed that at least part of the ubiquinone binding pocket and possibly the proton translocation machinery of complex I have evolved from the domains surrounding the [NiFe] site of the hydrogenase (14).…”
mentioning
confidence: 99%